Educational inequalities in blood pressure and cholesterol screening in nine European countries. Issue 11 (12th January 2012) - Rodin, Danielle; Stirbu, Irina; Ekholm, Ola; Dzurova, Dagmar; Costa, Giuseppe; Mackenbach, Johan P; Kunst, Anton E
Abstract : Background: To perform the first European overview of educational inequalities in the use of blood pressure and cholesterol screening. Methods: Data were obtained on the use of screening services according to educational level from nationally representative cross-sectional surveys in Belgium, Czech Republic, Denmark, Estonia, Finland, Hungary, Italy, Latvia and Lithuania. Screening rates were examined in the preceding 12 months and 5 years, for respondents 35+ years (45+ for women). ORs comparing low- to high-educated respondents were estimated using logistic regression controlling for age. Results: Inequalities in cholesterol screening favouring higher socioeconomic groups were demonstrated with statistical significance among men in four countries, whereby men with higher education were more likely to receive screening, with 1.22 as the highest OR. Among women, a similar pattern was found. Inequalities in blood pressure screening were even smaller and less often statistically significant. Hungary was the only country with higher rates of both types of screening in the low-educated group. In other countries, pro-high inequalities were slightly increased after controlling for self-rated health. Conclusions: All European countries in this study had small educational inequalities in the utilisation of blood pressure and cholesterol screening. These inequalities are smaller than those previously observed in the USA. Further comparative studies need to distinguish between screening for preventive purposes and screening for treatment and control.